Fundamentals of Entrepreneurship ENT300 Business Name: Last Minute / Fildza Ali Omar...[et al.] - Omar, Fildza; Rosli, Nur Ardini; Mohd Talib, Puteri Khalida; Abd Hamid, Nuraini; Abdullah, Nur Ainisa Shafina (2020)
Our company name is Last Minute Enterprise. We choose the name ‘Last Minute’ because these words are aligned as all the students often complete their work at the last minute. Our company located at Permatang Pauh, Pulau Pinang which are the most strategic place and highly demand in printing services because our company are located near at educational institutions such as UiTM Pulau Pinang, Politeknik Seberang Perai, Seberang Jaya Community College and SMK Pauh Jaya. We are offering printing services that can provide the best quality in printing services. We hope that our company have an opportunity in the future to cater the market in printing services.